Effects of dual-task paradigm on the injury potential during landing among individuals with chronic ankle instability - Zhong, Cheng; Luo, Xin; Gao, He; Zhang, Teng; Zhu, Xiaoxue; Huang, Xueke; Shen, Peixin (Frontiers in Physiology, 2024)
PurposeChronic ankle instability (CAI) causes maladaptive neuroplastic changes in the central nervous system, which may lead to high injury potential under dual-task conditions. This study aims to explore the effects of dual-task paradigm on the injury potential during landing among individuals with CAI.MethodsTwenty participants with CAI (4 female and 16 male, 12 were affected with their right limbs and 8 were affected with their left limbs, 20.4 ± 1.7 years, 176.9 ± 5.0 cm, and 72.0 ± 11.1 kg) and eighteen without CAI (6 female and 12 male, 20.2 ± 1.5 years, 173.5 ± 7.0 cm, and 70.3 ± 10.8 kg) were recruited. They drop-landed on a trap-door device, with their affected or matched limbs on a flippable platform, under single- (drop-landing only) and dual-task (drop-landing while subtracting of serial threes) conditions. A twelve-camera motion capture system was used to capture the kinematic data. Two-way ANOVA with mixed design (CAI vs non-CAI groups by single-vs dual-task conditions) was used to analyze the data.ResultsSignificant group-by-condition interactions were detected in the ankle inversion angle (P = 0.040, η2p = 0.012) and ankle inversion angular velocity (P = 0.038, η2p = 0.114). Both indicators decreased among individuals without CAI from single-to dual-task conditions, while remained unchanged among those with CAI; and they were higher among individuals with CAI under both single- and dual-task conditions, compared to those without CAI.ConclusionIndividuals with CAI have a reduced ability to limit ankle inversion compared to those without CAI. Under dual-task conditions, individuals without CAI limited their ankle inversion, while those with CAI did not. Drop-landing, especially under dual-task conditions, poses a high risk of excessive ankle inversion for individuals with CAI.